Analisis Framing Dugaan Korupsi Anas Urbaningrum dalam Kasus Wisma Atlet pada Harian Kompas dan Jawa Pos - Tesa Herowana; Sumekar Tanjung (Jurnal Komunikasi, 2012)
In 2012, Indonesian Corruption Eradication Comission (KPK) investigate further to Nazaruddin statement about Anas Urbaningrum’s corruption assessment on the sport center case. The frame analysis is used to look how Jawa Pos and Kompas Daily cover Anas Urbaningrum corruption assessment. This study concerns on Jawa Pos and Kompas Daily Januari editions 2012 about this news. It find that Jawa Pos Daily presents the Anas Urbaningrum’s news with resolute. While Kompas Daily presents that news with irresolute.